Metal nanoparticles as nano-sized opto-acoustic transducers - Fuentes Dominguez, Rafael (2018)
There has been much interest in the optical and mechanical properties of metal nanostructures and the possibility to use them as very high frequency opto-acoustic transducers. This interest stems from the ability of such devices to work as sources of ultrasound when a short optical pulse is used to thermally excite them producing GHz acoustic waves. This vibrational response can be detected in the time domain (with other short optical pulse) by measuring the changes in the scattered light using a technique called time-resolved pump-probe spectroscopy. In particular, these devices may allow the generation of ultrasound with very high spatial frequencies (short wavelengths and oblique directions) that will enable very high resolution imaging.